TV set DyTAES / YAAY DUND: Integration of agroecology in the revision of the Law on Agro-Sylvo-Pastoral Orientation (LOASP), Event Report - Belmin, Raphael; Mbodj, Absa (2024)
As part of its 5-year anniversary celebrations, the « Dynamique pour une Transition Agroécologique au Sénégal » (DyTAES) network organised a televised round table to discuss the issues, challenges and opportunities involved in integrating agroecology into the current revision of the Loi d'Orientation Agro-Sylvo-Pastorale et Halieutique (LOASP).